A Cross-Sectional Survey of Knowledge, Attitude, and Practices of University Students in Pakistan Regarding COVID-19 - Raza, Sohail; Mukhtar, Nadia; Nawaz, Muhammad; Ali, Muhammad Asad; Shabbir, Muhammad Abu Bakr; Ashraf, Muhammad Adnan; Ali, Zeeshan; Saleem, Muhammad Rizwan; Latif, Rabia; Yaqub, Tahir (Frontiers in Public Health, 2021)
COVID-19 pandemic is striking the world with its serious public health and socioeconomic complications. COVID-19 pandemic has influenced all forms of the life together with educational institutions. Therefore this cross-sectional survey was conducted to understand knowledge, attitude and practice related to COVID-19 in the students of University of Veterinary and Animal Sciences, Lahore. The data was collected using online self-directed questionnaire. The survey form includes six items about sociodemographic characteristics, 14 knowledge based questions, seven question on attitude and eight questions on practices. The sample number was calculated using Raosoft sample size calculator. A total number of 3854 students, including male 1823; female 2031, were engaged in this survey, having student representation from all provinces of the country. The data was analyzed using chi square test. Total 97% of the students know that etiological agent of COVID-19 is virus and it’s a disease of respiratory system (94%). Many students kept visiting their relatives during the lockdown (45%) and their relatives kept visiting them at home (59%). The student’s response varied a lot on specific questions about the transmission of virus. Female students had less information regarding the travel precautionary measures (p<0.01) but supplemental knowledge of prevention of disease from the positive patients (p<0.01). Conclusively, majority of the university students have had imperative knowledge, good attitude and active practice in response to COVID-19 outbreak. Moreover, the KAP scores have varied by demography, gender and number of family members. Therefore, continuous awareness on preventive behaviors should disseminate regularly in emergencies.